2023
DOI: 10.1038/s41467-023-37618-2
|View full text |Cite
|
Sign up to set email alerts
|

Active site recovery and N-N bond breakage during hydrazine oxidation boosting the electrochemical hydrogen production

Abstract: Substituting hydrazine oxidation reaction for oxygen evolution reaction can result in greatly reduced energy consumption for hydrogen production, however, the mechanism and the electrochemical utilization rate of hydrazine oxidation reaction remain ambiguous. Herein, a bimetallic and hetero-structured phosphide catalyst has been fabricated to catalyze both hydrazine oxidation and hydrogen evolution reactions, and a new reaction path of nitrogen-nitrogen single bond breakage has been proposed and confirmed in h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Recent breakthroughs provide a potential solution to the persistent challenge of an anodic OER by using thermodynamically more favorable electrocatalytic oxidation of small molecules, for instance, urea, hydrazine, polysulfide, benzyl alcohol and 5-hydroxymethyl furfural, which can result in a substantial reduction in cell voltage required for H 2 production. Among these alternatives, the polysulfide oxidation reaction (SOR, S x 2– + S 2– → S x +1 2– + 2e – ) stands out due to its markedly lower theoretical potential of −0.48 V vs RHE compared to that of the OER. , Notably, the SOR coupled with a cathodic hydrogen evolution reaction (HER) for H 2 production generates high-valence polysulfides in solution as the sole byproduct, which is much safer compared to water splitting yielding a potentially explosive mixture of H 2 and O 2 . , Importantly, this approach avoids the costly decomposition of small-molecule organics into low-value products like N 2 and CO 2 . , Several pioneering studies have made significant progress in SOR-assisted H 2 production. For instance, Deng et al demonstrated that nitrogen-doped graphene encapsulating a CoNi nanoalloy could initiate the anodic reaction at an onset potential of 0.25 V vs RHE, which was 1.24 V lower than that needed for the OER .…”
Section: Introductionmentioning
confidence: 99%
“…Recent breakthroughs provide a potential solution to the persistent challenge of an anodic OER by using thermodynamically more favorable electrocatalytic oxidation of small molecules, for instance, urea, hydrazine, polysulfide, benzyl alcohol and 5-hydroxymethyl furfural, which can result in a substantial reduction in cell voltage required for H 2 production. Among these alternatives, the polysulfide oxidation reaction (SOR, S x 2– + S 2– → S x +1 2– + 2e – ) stands out due to its markedly lower theoretical potential of −0.48 V vs RHE compared to that of the OER. , Notably, the SOR coupled with a cathodic hydrogen evolution reaction (HER) for H 2 production generates high-valence polysulfides in solution as the sole byproduct, which is much safer compared to water splitting yielding a potentially explosive mixture of H 2 and O 2 . , Importantly, this approach avoids the costly decomposition of small-molecule organics into low-value products like N 2 and CO 2 . , Several pioneering studies have made significant progress in SOR-assisted H 2 production. For instance, Deng et al demonstrated that nitrogen-doped graphene encapsulating a CoNi nanoalloy could initiate the anodic reaction at an onset potential of 0.25 V vs RHE, which was 1.24 V lower than that needed for the OER .…”
Section: Introductionmentioning
confidence: 99%
“…The ever-growing consumption of fossil fuels and associated serious environmental concerns have prompted the search for clean and renewable energy sources. Hydrogen (H 2 ), as the energy carrier with a high energy density and zero carbon dioxide emission, is regarded as an ideal candidate to replace existing natural fuel. Thus, it is one of the main tasks to exploit an environmental-friendly and efficient route to produce H 2 , among which water splitting is regarded as a feasible and promising technology. However, the oxygen evolution reaction (OER) occurring in the anode (OER, 4OH – → O 2 + 2H 2 O + 4e – , 1.23 V vs RHE) involves a four-electron-transfer process with intrinsically sluggish kinetics and high thermodynamic energy barrier formed by O–O bond, resulting in a high voltage of more than 1.23 V for a electrochemical water splitting toward hydrogen production. Most efforts have been focused on designing advanced and low-cost electrocatalysts to reduce the thermodynamic barriers for hydrogen evolution reaction (HER, 4H 2 O + 4e – → 2H 2 + 4OH – ) and OER, unfortunately, which still requires a very high voltage. …”
Section: Introductionmentioning
confidence: 99%
“…3,4 In facing of the serious challenges posed by climate change and the rising global demands for energy, it is essential to find and develop clean and sustainable energy sources. 5,6 Hydrogen energy is regarded as the most prospective energy carriers due to its clean, renewable and abundant natural reserves. 7,8 Water electrolysis has attracted more and more attention because it give rise to clean, sustainable hydrogen energy sources.…”
Section: ■ Introductionmentioning
confidence: 99%